2023
DOI: 10.3390/cells12020254
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Ascorbate in Combination with Anti-PD1 Checkpoint Inhibition as Treatment Option for Malignant Melanoma

Abstract: Ascorbate acts as a prooxidant when administered parenterally at high supraphysiological doses, which results in the generation of hydrogen peroxide in dependence on oxygen. Most cancer cells are susceptible to the emerging reactive oxygen species (ROS). Accordingly, we evaluated high-dose ascorbate for the treatment of the B16F10 melanoma model. To investigate the effects of ascorbate on the B16F10 cell line in vitro, viability, cellular impedance, and ROS production were analyzed. In vivo, C57BL/6NCrl mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Clinical trials using ascorbate intervention in patients with melanoma have not yet been reported, but results from animal studies are encouraging. Melanomas grew more slowly and were rejected more effectively [ 40 , 41 ] in ascorbate-treated mice, and immunotherapy treatment against melanoma tumours was enhanced by ascorbate injections in mice [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials using ascorbate intervention in patients with melanoma have not yet been reported, but results from animal studies are encouraging. Melanomas grew more slowly and were rejected more effectively [ 40 , 41 ] in ascorbate-treated mice, and immunotherapy treatment against melanoma tumours was enhanced by ascorbate injections in mice [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a very recent study published, Burkard et al were able to verify the efficacy of high dose AA to kill melanoma cells both in vitro and in vivo; and how it also exert their effect either alone or in combination with the anti-mouse checkpoint inhibitor antibody synergistically. 122 In another study, Luchtel et al showed that the combination of AA with a checkpoint inhibitor could have significant activity in cancer treatment. Their evaluation was the combination of high dose AA with a checkpoint inhibitor in a lymphoma mouse model.…”
Section: Aa and Cancer Immunotherapymentioning
confidence: 99%
“…In pre-clinical studies, AA has been shown to have synergism with checkpoint inhibitors. 122,123 AA has also been shown to synergistically potentiate the cytotoxicity of targeted therapies ibrutinib, venetoclax and idelalisib in CLL. 188 Further clinical investigations would be needed to determine the clinical benefits.…”
Section: Time For a Second Look?mentioning
confidence: 99%